Analisis Penerapan ISO 9001:2015 pada Proyek Rancang Bangun Rusunami TOD Tanjung Barat: Analysis of the Implementation of ISO 9001:2015 in the TOD Tanjung Barat Rusunami Design Project - Yanto, Heri; Guspari, Oni (Universitas Jember, 2025)
PT Brantas Abipraya (Persero), a state-owned enterprise in the construction sector, is responsible for implementing the Design and Build project of Rusunami TOD Tanjung Barat. The study focuses on assessing the quality management system in accordance with ISO 9001:2015. To collect the necessary information, surveys and interviews with relevant staff were carried out. Compliance with ISO 9001:2015 requirements, particularly clauses 4 to 10, was measured using a Likert scale. The assessment results indicate that the project has reached a maturity level between three and four. At this stage, the quality management system can be considered reasonably satisfactory, reflecting adequate implementation of standard practices. However, the expected maturity stage of five has not yet been achieved. To reach the desired outcome, several improvements are required. The organization needs to enhance employee competencies, prepare effective financial planning, ensure active managerial involvement, monitor customer satisfaction, and optimize infrastructure and resources. In addition, tracking quality objectives, developing new products, evaluating potential risks, and conducting awareness campaigns for staff regarding the quality management system are necessary to ensure continuous improvement and achievement of the highest maturity level. Abstrak Salah satu proyek yang dilakukan oleh PT Brantas Abipraya (Persero) yang berlokasi di industri konstruksi adalah Inisiatif Peningkatan Desain Konstruksi Rusunami TOD Tanjung Barat. Topik utama diskusi adalah hasil evaluasi sistem manajemen mutu berdasarkan ISO 9001:2015 untuk implementasi Desain dan Konstruksi Rusunami TOD Tanjung Barat. Untuk melakukan ini, kuesioner dan wawancara pembagian dilakukan dengan melibatkan staf yang bersangkutan. Implementasi standar ISO 9001:2015 (halaman 4–10) dapat dievaluasi pada tingkat variabel menggunakan skala Likert. Berdasarkan hasil data implementasi ISO 9001:2015 untuk proyek konstruksi Rusunami TOD Tanjung Barat, diperoleh level kematangan 3 hingga 4. Dari level kematangan 3 hingga 4 ini, dapat disimpulkan bahwa sistem manajemen mutu yang telah diterapkan sudah cukup baik. Namun, level yang dicapai belum memenuhi tujuan bisnis yang diharapkan, yaitu level 5. Untuk mencapai tujuan ini, perusahaan harus mengevaluasi kapabilitas SDM, penyusunan anggaran yang presisi, kesadaran manajemen, kepuasan konsumen, optimalisasi sarana dan prasarana, evaluasi target mutu, inovasi produk, dan risiko mutu, serta perlu mensosialisasi sistem manajemen mutu kepada seluruh karyawannya.